2009
DOI: 10.1021/ac801946s
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Relevant Online Electrochemical Method for Continuous and Simultaneous Monitoring of Striatum Glucose and Lactate Following Global Cerebral Ischemia/Reperfusion

Abstract: This study demonstrates a new electroanalytical method with a high physiological relevance for simultaneous online monitoring of glucose and lactate in the striatum of the rat brain following global cerebral ischemia/reperfusion. The online analytical method is based on the efficient integration of in vivo microdialysis sampling with an online selective electrochemical detection with the electrochemical biosensors with dehydrogenases, i.e., glucose and lactate dehydrogenases, as recognition elements. The dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 87 publications
6
72
0
1
Order By: Relevance
“…Another significant advance is the work by Lin et al, in which a sensor was devised for continuous and simultaneous monitoring of glucose and lactate in rat brain tissue. [164] The research group prepared a complex electroanalytical system in which SWNTs were loaded with glucose dehydrogenase or lactate dehydrogenase, respectively, for realtime monitoring of the metabolic intermediate glucose or the circulatory impairment molecule lactate.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…Another significant advance is the work by Lin et al, in which a sensor was devised for continuous and simultaneous monitoring of glucose and lactate in rat brain tissue. [164] The research group prepared a complex electroanalytical system in which SWNTs were loaded with glucose dehydrogenase or lactate dehydrogenase, respectively, for realtime monitoring of the metabolic intermediate glucose or the circulatory impairment molecule lactate.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…The carbon nanotube coating on the electrodes were biocompatible and enhanced both recording and electrical stimulation of neurons in vitro in cell culture, as well as in vivo in rats and monkeys, by decreasing the electrode impedance and increasing charge transfer. Lin et al [85] reported an electrochemical sensor devised for the continuous and simultaneous monitoring of glucose and lactate in rat brain tissue. This study included a complex electroanalytical system in which SWNTs were loaded with glucose dehydrogenase or lactate dehydrogenase were prepared for real-time monitoring of the metabolic intermediate, glucose, or the circulatory impairment molecule, lactate.…”
Section: Electronic and Electrochemical Sensorsmentioning
confidence: 99%
“…As a continuation of our interests, this study demonstrates an effective electrochemical approach to continuous measurements of cerebral HX by integrating online selective electrochemical biosensing with in vivo microdialysis. As reported previously [10][11][12][13] , the efficient integration of selective electrochemical detection with in vivo microdialysis has offered a cost-effective, less technically demanding and reliable approach to probing brain chemistry. To accomplish the selective detection of HX, xanthine oxidase was used as the recognition element and Prussian blue was used as the electrocatalyst for the detection of H 2 O 2 produced from the enzymatic reaction, since, as the artificial peroxidase, Prussian blue can catalyze the reduction of H 2 O 2 stably and efficiently [14][15][16] , allowing the detection of H 2 O 2 at a potential far from the redox potentials of electroactive species commonly existing in the cerebral systems, such as ascorbic acid, uric acid, and 3,4-dihydroxyphenylacetic acid, as reported in our earlier study [13] .…”
Section: Introductionmentioning
confidence: 91%
“…Motivated by the desire to understand the chemical essence of the physiological processes, we have focused our interests on the development of new experimental protocols with a high spatial and temporal resolution to probe brain chemistry mainly through interdisciplinary efforts combining electrochemistry with physiology [10][11][12] . As a continuation of our interests, this study demonstrates an effective electrochemical approach to continuous measurements of cerebral HX by integrating online selective electrochemical biosensing with in vivo microdialysis.…”
Section: Introductionmentioning
confidence: 99%